Effectiveness of Jacobson’s Progressive Muscle Relaxation in Reducing Anxiety and Depression in Hospitalised AIDS Patients - Kambu, Yowel (Scripta Medica, 2025)
Background/Aim: Hospitalised patients with AIDS frequently experience anxiety and depression due to social stigma, prognostic uncertainty, and the physiological effects of the disease. These conditions can adversely affect the quality of life and treatment adherence. A relaxation method known as Jacobson’s Progressive Muscle Relaxation (JPMR) has shown efficacy in alleviating stress and anxiety across various medical conditions. However, evidence regarding JPMR’s efficacy of JPMR in patients with AIDS remains limited, particularly in Indonesia. The research sought to assess the efficacy of JPMR in alleviating anxiety and depression amongst AIDS patients in hospital settings. Methods: This study employed a randomised controlled trial (RCT) with a pretest-posttest design conducted at Dr. Jhon Piet Wanane General Hospital, Sorong Regency, Southwest Papua. The study involved 52 AIDS patients who fulfilled the selection criteria. These participants were divided equally and randomly into two groups: the intervention group (n = 26) and the control group (n = 26). Participants in the intervention group engaged in JPMR sessions lasting 20-30 minutes, twice per day for a period of 10 days. In contrast, the control group received only routine care. The Patient health questionnaire anxiety and depression scale (PHQ-ADS) was utilised to assess anxiety and depression levels both before and after the intervention. Statistical analysis was conducted using paired and independent t-tests to evaluate the results. Results: The study findings revealed a notable decrease in PHQ-ADS scores amongst the intervention group when compared to the control group (p<0.001). Several factors were found to significantly contribute to elevated anxiety and depression scores in AIDS patients receiving hospital care. These included co-occurring tuberculosis (TBC), insufficient social support, prior mental health conditions, and alcohol use, with respective p-values of 0.04, 0.002, 0.001, 0.07, and 0.05. Conclusion: Research indicates that JPMR serves as an efficacious non-drug treatment for alleviating anxiety and depression amongst AIDS patients in hospital settings. These results advocate for the incorporation of JPMR into psychosocial care programmes within hospitals. Additional studies involving a larger patient group are necessary to validate these outcomes.